Pengaruh Disiplin Dan Motivasi Terhadap Kepuasan Kerja Karyawan - Dhuha Safria; Purwatiningsih Purwatiningsih; Alan Budi Kusuma; Frida Aprillia (CV. Ulil Albab Corp, 2024)
This study aims to analyze the influence of discipline and motivation on employee job satisfaction at CV. ABC. Using a quantitative approach with a descriptive method, data were collected through a Likert scale questionnaire distributed to 30 employees during the period of July to September 2024. Data analysis was conducted using multiple linear regression with SPSS software version 26. The results indicate that there is a positive and significant effect of discipline and motivation on job satisfaction, both partially and simultaneously. Based on these findings, it is recommended that the company enhances discipline through a clear system of rewards and sanctions as well as regular performance evaluations. To increase motivation, the company is advised to provide recognition for achievements and offer career development opportunities. Implementing these strategies is expected to improve overall employee job satisfaction.